Ghrelin and obestatin levels in hypertensive obese patients. (December 2014) - Wang, Wei-Min; Li, Shu-Mei; Du, Fu-Man; Zhu, Zhi-Cheng; Zhang, Ji-Chang; Li, Yang-Xue
Objectives: To investigate plasma total ghrelin and obestatin levels and the ghrelin/obestatin ratio prospectively, in hypertensive obese patients. Methods: Height, weight, and waist and hip circumferences were measured in hypertensive and normotensive obese patients and matched healthy controls; the body mass index and waist to hip ratio were calculated. Fasting glucose and insulin levels were measured and the homeostasis model assessment of insulin resistance (HOMA-IR) was determined. Fasting ghrelin and obestatin concentrations were measured by radioimmunoassay and the ghrelin/obestatin ratio was calculated. Results: A total of 38 hypertensive obese patients, 40 normotensive obese patients and 38 controls were enrolled. Hypertensive obese patients had lower plasma levels of ghrelin and obestatin than normotensive obese patients or controls. In addition, normotensive obese patients had lower plasma ghrelin and obestatin levels than controls. In hypertensive obese patients, ghrelin and obestatin levels were negatively associated with systolic and diastolic blood pressure, fasting insulin and HOMA-IR. In normotensive obese patients, ghrelin, obestatin and the ghrelin/obestatin ratio were negatively associated with fasting insulin and HOMA-IR. In both patient groups, fasting obestatin and ghrelin concentrations were significantly and positively correlated with each other. Conclusion: Changes in the levels of ghrelin and obestatin may play a role in the pathophysiology of obesity and hypertension.